Type of helminth parasite in Snakehead fish (Channa striata) from Seuneubok Cina, Indra Makmur, Aceh Timur, Indonesia - Masitta Tanjung (International Journal of Ecophysiology, 2019)
Snakehead fish (Channa striata) is one of the freshwater fish in tropical regions such as Asia and Africa, and has high nutrition but is difficult to cultivate. In Indonesia, Snakehead fish are found in paddy fields, swamps and ditches, making them susceptible to parasites. Constraints in Snakehead fish cultivation are caused by the nature of the fish as a predatory, lack of the availability of food and environmental conditions that can affect the growth of the fish. The former paddy fields in Seuneubok Cina of Indra Makmur, Aceh Timur, Indonesia, is found many Snakehead fish. This research aims to determine the types of parasites that infect Snakehead fish. The Snakehead fish was taken using electrofishing gear with purposive sampling method, then dissected and identified the endoparasites which contained in the fish intestines. The research results found three genus of parasites: Pallisentis, Procamallanus and Camallanus.